Smart Street Light Working and Power Supply Monitoring System - R.Saravanan, Dr.; Periyasamy, R.; Mohanarangam, S.; Tamilarasan, M.; Dakshnamoorthy, D. (International Journal of Engineering and Technology, 2026)
Even though only a small portion of all travel occurs between 7pm and 8am, yet this time duration takes responsibility for 40% of death, serious injuries and road accidents. Street lighting is the prominent solution that reduces the risk of all road users such as drivers, riders, and pedestrians during the hours of darkness. This paper intends to reduce dissipated man power needed to manage the automated switching on/off, monitoring the current status of lights after fixation. The system includes a set of light sensors like LDR at each street light node to monitor the degradation of the lights and the alerts are transmitted directly to the concerned Zone ADE through IOT based remote application and to the direct workers through GSM based SMS by the system. The system aims direct remote monitoring and immediate repair intimation of lights in a user friendly and effective manner.